2013
DOI: 10.3855/jidc.3453
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli and Salmonella spp. in meat in Jeddah, Saudi Arabia

Abstract: Introduction: Food-borne pathogens are the leading cause of illness and death in developing countries, killing approximately 1.8 million people annually. In developed countries, food-borne pathogens are responsible for millions of cases of infectious gastrointestinal diseases each year, costing billions of dollars. The objective of this study was to screen for two major food-borne pathogens, Escherichia coli and Salmonella spp., from meat samples obtained from different strata of the consumer market in Jeddah.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Observations of the current state of animal slaughter and processing in Saudi Arabia suggests that hide to carcass transfer is occurring and no antimicrobial intervention measures to reduce the level of pathogens on carcasses as used in the United States are in place. This is supported by a recent report by Iyer et al (20) of E. coli and Salmonella isolated from nonspecified meats collected from market places in Jeddah, KSA.…”
Section: 05)supporting
confidence: 76%
“…Observations of the current state of animal slaughter and processing in Saudi Arabia suggests that hide to carcass transfer is occurring and no antimicrobial intervention measures to reduce the level of pathogens on carcasses as used in the United States are in place. This is supported by a recent report by Iyer et al (20) of E. coli and Salmonella isolated from nonspecified meats collected from market places in Jeddah, KSA.…”
Section: 05)supporting
confidence: 76%
“…Salmonellosis is a widespread foodborne zoonosis in many countries (Wegener and Baggesen, 1996;Lo Fo Wong, 2002;Iyer et al, 2013); people of all ages are affected, and the incidence is highest in children. In the developing world, human immunodeficiency virus infection and AIDS are important risk factors for nontyphoidal salmonellosis and bacteremia (Obi and Bessong, 2002); and several studies have shown in infected African adults with documented bloodstream infections that nontyphoidal salmonellae were isolated from up to 35% of adults (Hohmann, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional microbiological methods for detection of these bacteria, however, usually include multiple subcultures and biotype or serotype identification steps and, thus are laborious and time-consuming [ 9 ]. With the development of molecular techniques, polymerase chain reaction (PCR) has become an important tool for detecting pathogenic microorganisms in food products which improved the sensitivity, specificity, and speed of detection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%